Physical characteristics of Canadian Arctic reference lakes described in Campana et al (2020; Suppl Table 1 in Nature Climate Change) - Steven Campana (Knowledge Network for Biocomplexity, 2020)
Supplementary Table 1. Physical characteristics and sample summary of the reference lakes used to calibrate the lake trout population dynamics models. All values were observed except estimated values indicated by *